PENEGAKAN HUKUM TERHADAP PELAKU KEJAHATAN PEMBAKARAN HUTAN DALAM SISTEM PERADILAN PIDANA DI INDONESIA - Fadillah Zulkarnaen; Maryano Maryano; Achamd Fitrian (SINERGI : Jurnal Riset Ilmiah, 2026)
This study highlights the gap between strict regulation and the reality of court decisions, and seeks an ideal law enforcement model for individual and corporate actors. The formulation of the problem in the research in this paper is how the application of legal sanctions against perpetrators of forest burning crimes in the criminal justice system and how the ideal concept of the application of legal sanctions against perpetrators of forest burning crimes in the criminal justice system in Indonesia. The study used a normative juridical approach that emphasizes literature research. In this study used is the approach of legislation, conceptual approach, case approach, and the source of legal materials used are primary, secondary and tertiary legal materials used qualitative analysis. Based on the results of the study showed that the criminal justice system in Indonesia has formulated the threat of layered sanctions for perpetrators, both individuals and corporations, in the form of imprisonment and fines. However, in practice, the application of these sanctions still faces a number of obstacles, such as weak coordination between law enforcement agencies, evidence of intentional elements, and law enforcement against intellectual or corporate actors which is often not optimal. Therefore, a progressive and comprehensive optimization of the law is needed, including the use of scientific evidence and strict sanctions to recover environmental losses